Perceptions and Decision-Making Regarding Childfree Choices Among College Students in Indonesia: A Study at Universitas Islam Negeri Sunan Gunung Djati Bandung - Putra, Raafi Herdiansyah; Iqbal, Asep Muhamad; Irwandi, Irwandi (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2024)
This article examines the perceptions and decision-making processes regarding the concept of being childfree (choosing to live without children) among students at Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung. This university provides a compelling case for study due to its mission of cultivating mentally, spiritually, and intellectually capable individuals. The emphasis on 'spirituality' highlights the expectation for UIN Bandung students to develop a strong understanding of religion, which influences decision-making, including on social and religious issues such as the childfree phenomenon. This study seeks to explore UIN Bandung students’ perceptions of the childfree phenomenon, identify the factors influencing these perceptions, and analyze their decision-making processes regarding childfree choices. Using a descriptive method with a mixed-methods approach, data were collected through surveys and unstructured interviews. The findings reveal that the majority of UIN Bandung students perceive the concept of being childfree negatively. Factors influencing their perceptions include internal factors, such as personality traits (attitudes, interests, and experiences), and external factors, such as societal conditions. The study categorizes student decision-making into three groups: those who perceive childfree negatively and desire to have children, those who perceive childfree positively and choose to remain childfree, and those who perceive childfree positively but still desire to have children.